Regarding taking necessary precautions against coronavirus - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request to take necessary precautions against coronavirus to prevent contamination during BRACU new campus project work.